2010
DOI: 10.1158/0008-5472.can-09-4283
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Integrin α3β1 in Breast Cancer Cells Reduces Cyclooxygenase-2 Gene Expression and Inhibits Tumorigenesis, Invasion, and Cross-Talk to Endothelial Cells

Abstract: Integrin receptors for cell adhesion to extracellular matrix have important roles in promoting tumor growth and progression. Integrin α3β1 is highly expressed in breast cancer cells where it is thought to promote invasion and metastasis; however, its roles in regulating malignant tumor cell behavior remain unclear. In the current study, we used short-hairpin RNA (shRNA) to show that suppression of α3β1 in a human breast cancer cell line, MDA-MB-231, leads to decreased tumorigenicity, reduced invasiveness, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
105
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(126 citation statements)
references
References 48 publications
16
105
4
1
Order By: Relevance
“…5B and 5C). It has been reported that integrin ␣3␤1 promotes radiation-induced migration of meningioma cells and that suppression of integrin ␣3␤1 inhibits tumorigenesis and invasion in breast cancer cells (66). Our transwell assay on the ITGA3 knockdown cells also supported the same conclusion.…”
Section: Analysis Of Identified Glycoproteins Enriched Via Erlic-supporting
confidence: 87%
“…5B and 5C). It has been reported that integrin ␣3␤1 promotes radiation-induced migration of meningioma cells and that suppression of integrin ␣3␤1 inhibits tumorigenesis and invasion in breast cancer cells (66). Our transwell assay on the ITGA3 knockdown cells also supported the same conclusion.…”
Section: Analysis Of Identified Glycoproteins Enriched Via Erlic-supporting
confidence: 87%
“…Preclinical studies have shown that a3b1 promotes malignant behavior of breast cancer cells in vivo and in vitro (Cagnet et al, 2013;Mitchell et al, 2010;Morini et al, 2000;Scales et al, 2013;Sugiura and Berditchevski, 1999;Wang et al, 2004), as well as skin tumorigenesis in vivo (Sachs et al, 2012), implicating this integrin as a potential therapeutic target to inhibit cancer progression and metastasis (Subbaram and DiPersio, 2011). Laminin-332, a major ECM ligand for a3b1, is often expressed highly in breast cancer cells, where it enhances motility (Carpenter et al, 2009;Carpenter et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Laminin-332, a major ECM ligand for a3b1, is often expressed highly in breast cancer cells, where it enhances motility (Carpenter et al, 2009;Carpenter et al, 2008). At least some functions of a3b1 in transformed or immortalized cells are attributable to the ability of a3b1 to regulate genes that stimulate invasive growth and/or angiogenesis, including matrix metalloproteinase-9 (MMP-9) (Iyer et al, 2005;Morini et al, 2000) and cyclooxygenase (Cox-2, also known as prostaglandin G/H synthase 2 in human) (Mitchell et al, 2010). In immortalized keratinocytes, a3b1-dependent-induction of MMP-9 occurs through a post-transcriptional mechanism of enhanced mRNA stability (Iyer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 is an inducible enzyme that interferes with tumor development and angiogenesis, related to the inhibition of apoptosis through inhibition of the proapoptotic Bax protein and overexpression of the antiapoptotic bcl-2 protein. COX-2 catalyzes the conversion of arachidonic acid to PGE2 and enhances the metastatic phenotype of both breast cancer cells in vitro and breast tumors (Mitchell et al, 2010;Miglietta et al, 2010). PGE2, the catalytic product of COX-2, may promote tumor development and angiogenesis (Boland et al, 2004;Miglietta et al, 2010;Yu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%